Global potential for seaweed aquaculture on existing offshore infrastructure - Finnley W.R. Ross; Martino E. Malerba; Peter I. Macreadie (Heliyon)
Seaweed aquaculture is growing 8.9 % annually to a forecast US$ 22.13 billion in 2024 and has several environmental, economic and social co-benefits. A proposed approach to expanding seaweed aquaculture is to develop offshore aquaculture. However, the costs of the infrastructure remain a key barrier. Reducing costs by growing seaweed on obsolete oil and gas infrastructure and offshore wind farms may make offshore seaweed cultivation economically viable, but the scale of opportunity needs to be clarified. We estimate an area of 53,387–106,774 ha is currently available to cultivate seaweed on offshore wind farms, which could yield 736,831–4,441,116 tonnes of dry seaweed annually. Existing offshore oil and gas infrastructure could create 1,357,530–5,430,120 ha for growing seaweed. Using 2019 seaweed prices, seaweed production on offshore wind farms and oil and gas infrastructure could return USD $3356 - $50,320 Million, sequester 687,784–8,616,449 tonnes of CO₂, and subsequent low carbon seaweed products could displace 987,642–33,221,364 tonnes of CO₂ emissions. While the scale of opportunity is significant, we caution that the regulatory and engineering costs of ‘keeping the lights on’ for decommissioned oil and gas infrastructure may make costs prohibitively high for seaweed cultivation. Even with existing infrastructure, the cost of cultivating seaweed offshore remains the largest barrier to implementation. A significant increase in market value for seaweed products is required to make offshore infrastructure economically viable. Similarly, many ecological and regulatory risks to offshore seaweed cultivation need to be further understood and minimised.